(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
Origin, distribution, relief of gray oasis soils in the territory of Surkhandarya region, lithologicalgeomorphological, hydrogeological conditions of the studied area and soil-forming factors and morphological features of soils, mechanical composition, nutrient supply.